Failure of 'therapeutic' doses of beta-adrenoceptor antagonists to alter the disposition of tolbutamide and lignocaine. - Miners, J O (1984)
The effects of separate 1 week pre-treatments with each of the beta-adrenoceptor antagonists, propranolol (80 mg every 12 h), metoprolol (100 mg every 12 h) and atenolol (50 mg once daily), on the disposition of a single i.v. dose of tolbutamide were studied in six healthy volunteers. In addition, the effects of a 1 week pre-treatment with metoprolol (100 mg every 12 h) and atenolol (50 mg once daily) on the disposition of orally and i.v. administered lignocaine were determined in seven healthy subjects. Tolbutamide clearance, half-life, volume of distribution and plasma protein binding were not altered by the beta-adrenoceptor blocker pre-treatments. Similarly, neither metoprolol nor atenolol had a significant effect on the systemic clearance, apparent oral clearance or other dispositional parameters of lignocaine. 'Therapeutic' plasma concentrations of the beta-adrenoceptor blockers were confirmed on each study day. It is concluded that the inhibition of oxidative drug metabolism previously reported for lipophilic beta-adrenoceptor blockers may be selective for different forms of cytochrome P450 and possible concentration-dependent.